Binding analysis of Bacillus thuringiensis Cry1 proteins in the sugarcane borer, Diatraea saccharalis (Lepidoptera: Crambidae) - Davolos, Camila C. [UNESP]; Hernandez-Martinez, Patricia; Crialesi-Legori, Paula C. B. [UNESP]; Desiderio, Janete A. [UNESP]; Ferre, Juan; Escriche, Baltasar; Lemos, Manoel Victor F. [UNESP] (Elsevier B.V., 2015)
Sugarcane borer (Diatraea saccharalis, F.) is an important corn pest in South America and United States. The aim of the present study was to analyze the susceptibility and binding interactions of three Cry1A proteins and Cry1Fa in a Brazilian D. saccharalis population. The results showed that Cry1Ab was the most active, followed by Cry1Ac,Cry1Fa and Cry1Aa. All Cry1-biotinylated proteins tested bound specifically to the D. saccharalis brush border membrane vesicles (BBMV). Heterologous competition assays showed shared binding sites for all Cry1A proteins and another one shared by Cry1Fa and Cry1Ab. Thus, pyramiding Cry1Aa/Cry1Ac and Cry1F proteins would be a recommended strategy for managing this pest. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Insect resistance management; Insect corn pest; Insecticidal proteins; Insect control; Binding site models